Voyage of theranostic liposomes for imaging and therapy. (19th May 2017) - Sachin, Mitkare; Sachin, Dolare; Dinesh, Sakarkar
ABSTRACT: Drug delivery is a critical issue in any disease treatment. Nowadays much more effort is being focused on integrating imaging agent and therapeutic drugs in a single formulation to achieve a simultaneous disease diagnosis and targeted drug delivery. This new terminology 'nanotheranostics' have been used to describe these nanoparticle formulations. In the ancient years, various nanocarriers (liposomes, nanoparticles, dendrimers, micelles, antibodies, etc.) have been studied for targeted delivery of chemical or biological molecules. In these nanocarriers, liposome is largely studied nanoscale delivery systems and offers more advantages than others due to their unique structural properties. This review will highlight theranostic concept as well as some examples of theranostic liposomal formulations in clinical or preclinical stages. We briefly reviewed approaches to formulate theranostic liposomal formulations.